Cytokine assays: role in evaluation of the pathogenesis of autoimmunity. - Feldmann, M; Brennan, F; Chantry, D; Haworth, C; Turner, M; Katsikis, P; Londei, M; Abney, E; Buchan, G; Barrett, K (1991)
Cytokines are protein mediators involved in inflammation, the immune response, cell growth, repair and fibrosis. All of these processes are ongoing in active autoimmune diseases such as rheumatoid arthritis (RA), and so it would be expected that many cytokines would be actively produced in RA joints or Graves' disease (GD) thyroid glands. The cDNA cloning of cytokines has permitted the generation of pure recombinant molecules, and of newer more sensitive assays, and spurred the rapid development of knowledge in this field. Here we review the molecular strategies devised to study the possible role of cytokines in the pathogenesis of RA and GD, and describe some of the initial results. After 'cataloguing' the relative abundance of various cytokines, we sought to discover which cytokines are of major importance in pathogenesis. For that purpose we used neutralizing anti-cytokine antibodies and found that TNF alpha is one of the major signals regulating the production of IL-1 in the RA but not in the osteoarthritic (OA) joint. In order to further understand the dynamics of the cytokine network, the localization of the cytokine-producing cells by immunostaining and in situ hybridization has also been performed. The latter techniques are particularly valuable for attempting to establish the role of the target cell, such as thyroid epithelium, in the pathogenesis of disease. Cytokines act on cells via binding to high-affinity receptors. The last two years has been the cDNA cloning of many molecules encoding cytokine receptor chains, and it is now possible to begin to evaluate the other half of the cytokine pathway. Taken together, there are now exciting opportunities for the molecular dissection of the cytokine events occurring in auto-immune tissues.